The Alqueva hydro-meteorologic experiment - Salgado, R. (2015)
The ALqueva hydro-meteorological experiment, ALEX 2014 (http://www.alex2014.cge.uevora.pt) was an integrated field campaign with measurements of chemical, physical and biological parameters at different experimental sites in the Alqueva reservoir and in its surrounding region. With the main purpose of studing the lake-atmosphere interactions, the ALEX 2014 took place form June to September and comprised a three days Intensive Observation Period (IOP) from 22 to 24 July.